Checking Rights: An IR Manager’s Guide to Checking Copyright - Baker, Stewart; Kunda, Sue (Journal of Copyright in Education & Librarianship, 2019)
Institutional repository (IR) managers often find themselves providing copyright guidance to faculty who wish to self-archive their published scholarship or to students depositing theses and dissertations. As IR managers may not be copyright experts themselves, making determinations and checking rights can be difficult and time-consuming. This article is intended as a practical guide to describe common types of material that can be placed in an IR as well as potential copyright issues and other considerations for each type. Material types covered include book chapters, journal articles, conference proceedings, student papers, electronic theses and dissertations, research data sets, historical and archival materials, and oral histories. Underlying issues such as copyright ownership, work made for hire, and the legal definition of publication are also discussed. For easier reference, the appendix contains a chart with brief descriptions of issues and resources.